Shifting Diets of Lake Trout in Northeastern Lake Michigan. (22nd July 2019) - Luo, Miles K.; Madenjian, Charles P.; Diana, James S.; Kornis, Matthew S.; Bronte, Charles R.
Abstract: Prey fish communities in Lake Michigan have been steadily changing, characterized by declines in both the quantity and quality of Alewife Alosa pseudoharengus . To evaluate concurrent changes in the diet of Lake Trout Salvelinus namaycush in northeastern Lake Michigan, we analyzed stomach contents of Lake Trout caught during gill‐net surveys and fishing tournaments from May through October 2016. We then compared the composition, on a wet‐weight basis, of 2016 diets with those previously described in a recent survey conducted in 2011. Overall, we found that Lake Trout diets in 2016 consisted mostly (94% by wet weight) of Alewives and Round Goby Neogobius melanostomus . Averaging across May through October, 61% of the Lake Trout diet consisted of Alewives. A clear seasonal shift was apparent: the diet was dominated by Round Goby (67%) during May–June, whereas Alewives dominated the diet (76%) during July–October. Seasonal dominance of Round Goby in spring Lake Trout diets has not been previously observed in northeastern Lake Michigan as Round Goby represented only 21% of the Lake Trout diet in spring of 2011. Diet composition of Lake Trout caught in gill nets did not significantly differ from diet composition of Lake Trout caught by anglers in either the May–June period or the July–October period. Although Lake Trout showed increased diet flexibility in 2016 compared with 2011, Alewives were still the predominant diet component during 2016, despite reduced Alewife biomass throughout Lake Michigan. Nonetheless, this further evidence of diet plasticity suggests that Lake Trout may be resilient to ongoing and future forage base changes.